2011
DOI: 10.1007/s00436-011-2726-4
|View full text |Cite
|
Sign up to set email alerts
|

The study of apoptotic bifunctional effects in relationship between host and parasite in cystic echinococcosis: a new approach to suppression and survival of hydatid cyst

Abstract: Cystic echinococcosis (hydatidosis) is a zoonotic helminthic disease of human and other intermediated hosts wherein infection is caused by the larval stages of tapeworm Echinococcus granulosus. Growth of the larval stage is formed throughout the internal organs, the liver and lung, causing their destruction. Important pathways are unknown about suppression and survival of cysts in human body. In this study, apoptotic bifunctional effects are evaluated in relationship between host and parasite in cystic echinoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Immunization may thus inhibit splenocyte apoptosis to thereby permit extensive splenocyte expansion and a severe cellular reaction, resulting in protective immunity and destruction of the parasite, as reported in our work. Additionally, in studying mechanisms of cyst survival, Spotin et al (2012) concluded that apoptosis of the germinal layer is a possible mechanism of suppression in hydatidosis patients, while lymphocyte apoptosis promotes cyst survival. Our results further validate this previous finding, as an increase in apoptotic markers in infertile cysts and decreased apoptosis of inflammatory cells was observed following immunization, leading to the destruction of the larval cestode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunization may thus inhibit splenocyte apoptosis to thereby permit extensive splenocyte expansion and a severe cellular reaction, resulting in protective immunity and destruction of the parasite, as reported in our work. Additionally, in studying mechanisms of cyst survival, Spotin et al (2012) concluded that apoptosis of the germinal layer is a possible mechanism of suppression in hydatidosis patients, while lymphocyte apoptosis promotes cyst survival. Our results further validate this previous finding, as an increase in apoptotic markers in infertile cysts and decreased apoptosis of inflammatory cells was observed following immunization, leading to the destruction of the larval cestode.…”
Section: Discussionmentioning
confidence: 99%
“…Several vaccine candidates for IHs have been tested and were shown to elicit variable degrees of protection (LIGHTOWLERS et al, 1996(LIGHTOWLERS et al, , 1999(LIGHTOWLERS et al, , 2000WOOLLARD et al, 1998). Although there has been extensive research into post-immunization antibody responses, other aspects of the vaccine-induced immune response remain unknown, including those that affect apoptotic changes underlying fertility, suppression and survival of hydatid cysts (SPOTIN et al, 2012). Research into apoptosis has increased substantially since the early 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of these markers in detecting more unknown haplotypes than nuclear-conserved gene (ITS1-rDNA) has already been proven (31,32). The existence of novel haplotypes in G1 and mixed genotypes is related to the pathogenicity range of Echinococcus spp., the creation of re/emergent strains in the region, and the resistance of metacestodes to host innate immunity responses (33)(34)(35). Additionally, genotyping analyses of all cattle isolates exhibited the G1 strain.…”
Section: Discussionmentioning
confidence: 99%
“…[42,61,62] Regarding C. rotundus and within this hypothesis, recent studies concluded that the aerial parts extract of this plant exhibit a potential use as antioxidant and apoptosis inducer and explained that the anti-proliferative effect of these extracts is due to induction of apoptosis and suggested the regulation of apoptotic genes may be controlled by their phenolic content, orientin is one of the main flavonoids identified in alcoholic extract. [33] Moreover, the result of Hu et al, [63] confirmed the presence of apoptosis and the existence of CED-3 like apoptotic gene in protoscoleces of E. granulosus and proved that H2O2and hexamenthasone can induce cell apoptosis of protoscoleces in drug-induced apoptosis mechanisms.…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 93%